Using the Endoscopic Endonasal Transclival Approach to Access Aneurysms Arising from AICA, PICA, and Vertebral Artery: An Anatomical Study - Doan, Vivian (J Neurol Surg B Skull Base, 2015)
Objective To explore the use of the endoscopic endonasal transclival approach (EEA) for clipping anterior inferior cerebellar artery (AICA), posterior inferior cerebellar artery (PICA), and vertebral artery (VA) aneurysms. Design Anatomical study. Participants Fifteen adult cadavers. Main Outcome Measures Length of artery exposed and distance from the nasal ala to the arteries. Results The length of the right and left VA exposed were 1.7 ± 0.6 cm and 1.6 ± 0.6 cm, respectively. The distance to the right VA was 11.1 ± 0.9 cm and to the left was 11.1 ± 0.8 cm. Right and left AICA were exposed for an average length of 1.1 ± 0.3 cm and 0.8 ± 0.3 cm, respectively. The distance to the right AICA was 10.3 ± 0.8 cm and to the left was 10.3 ± 0.8 cm. The right PICA was exposed for a length of 0.5 ± 0.2 cm at a distance of 10.9 ± 0.5 cm. The left PICA was exposed for a length of 0.5 ± 0.2 cm at a distance of 11.1 ± 0.9 cm. Conclusion The EEA can provide direct access to AICA, PICA, and VA, making it a potential alternative to the traditional approaches for the clipping of aneurysms arising from those arteries.